PENDIDIKAN KARAKTER MELALUI GENDING RARE STUDI ETNOGRAFI PADA ANAK USIA DINI DI DESA ADAT TENGANAN PEGRINGSINGAN, KABUPATEN KARANGASEM, PROVINSI BALI (2013) - SUDIANI, NI NYOMAN (Jurnal Pendidikan Usia Dini, 2015)
Abstract: The purpose of this study is to figure out how character education for early childhood carried out through gending rare, the place, time, and rhythm of gending rare is sung for character education to early childhood in Desa Adat Tenganan Pegringsingan. This study used a qualitative ethnographic research methods. The study found that the education of characters that can be educated through gending rare: individually such as: the religious character education, hard working, self-contained, responsibilities, strong, humble, honest, helpful, willing to sacrifice, and joyous; socially character education such as: character education togetherness, love of the homeland, and care for the environment.Character educationin early childhood through gending rare done at home, in the community and in schools, and parents sung during lull children, bathing the child, when the child is fed, and when of early childhood play with the peers or parents or guardians, and rhythm gending rare that play a role in character education in early childhood among others, melodious rhythm generally sung by parent, and rhythm chirpy when sung by early childhood during game play to add to the splendor. Keywords: character education, gending rare, early childhood